2021
DOI: 10.1016/j.jval.2020.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Examining Equity Effects of Health Interventions in Cost-Effectiveness Analysis: A Systematic Review

Abstract: This systematic review aims to catalogue and describe published applications of equity-informative costeffectiveness analysis (CEAs).Methods: Following PRISMA guidelines, we searched Medline for English-language, peer-reviewed CEAs published on or before August 2019. We included CEAs that evaluated 2 or more alternatives; explicitly mentioned equity as a consideration or decision-making principle; and applied an equity-informative CEA method to analyze or examine at least 1 equity criterion in an applied CEA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 92 publications
0
37
0
Order By: Relevance
“…When valuing therapeutics for a pandemic that has a disproportionate impact on particular subsets of the population, it is advisable to consider methods that can account for any differential impacts. The distributional form of cost-effectiveness analysis (DCEA) evaluates interventions with differential impacts on socioeconomic subgroups and compares the magnitude in each group [26,27]. In lieu of a full DCEA, which would require trial data or a decision-analytic model to empirically inform the distribution of effects, Love-Koh et al describe an aggregate DCEA for health technologies that rolls up existing data alongside a measure of inequality [28].…”
Section: Equitymentioning
confidence: 99%
“…When valuing therapeutics for a pandemic that has a disproportionate impact on particular subsets of the population, it is advisable to consider methods that can account for any differential impacts. The distributional form of cost-effectiveness analysis (DCEA) evaluates interventions with differential impacts on socioeconomic subgroups and compares the magnitude in each group [26,27]. In lieu of a full DCEA, which would require trial data or a decision-analytic model to empirically inform the distribution of effects, Love-Koh et al describe an aggregate DCEA for health technologies that rolls up existing data alongside a measure of inequality [28].…”
Section: Equitymentioning
confidence: 99%
“…Our recent systematic review found that the number of equity-informative CEAs is increasing, and they have been used to estimate the cost-effectiveness of interventions for a wide range of diseases in several countries. 11 We found that at least nine dimensions of health equity, from socioeconomic status to race and ethnicity, have been reflected in equity-informative CEAs to date. These results suggest that equity-informative CEAs have the potential to address various health equity concerns in CEA that several HTA agencies explicitly consider in their decision-making.…”
Section: Building On the Foundationsmentioning
confidence: 78%
“…HTA practitioners also need to consider how issues such as equity and affordability can be better incorporated into HTA methods to allay the concerns of those opposed to HTA. Though methods for the incorporation of equity into HTA have been developed, they remain underutilised [ 19 , 30 ]. Methods of communication with policymakers, researchers and civil society also need to be improved on these issues.…”
Section: Discussionmentioning
confidence: 99%